How Has Regional Integration Taken Place in Other Regions? : Lessons for South Asia - Kathuria, Sanjay (World Bank, Washington, DC, 2015)
As the momentum for multilateral trade liberalization has slowed, an increasing amount of liberalization is taking place at a regional level. As of April 2015, there are 406 regional trade agreements (RTAs) in force worldwide, more than double the number in force in 2000. These agreements cover over half of international trade. Countries engage in regional cooperation for a variety of reasons. First, it is easier to achieve agreement among a small number of regional partners than it is globally. Second, regional cooperation takes advantage of existing natural tendencies for regional trade that arise from geography and shared culture. This reinforces the regional division of labor already taking place among firms. Global value chains, in which lead firms organize a division of labor for complex products among many countries, often turn out to have a regional focus. Think, for example, of the electronics value chain in East Asia, and the automotive value chains focused on the United States, Germany, and Japan. South Asia itself is a small but growing part of value chains in textiles and apparel with both regional depth and cross-linkages to East Asia. This piece will focus on four aspects of trade liberalization (trade facilitation, non-tariff measures/barriers, intra-regional investment, and energy cooperation) that go beyond traditional preferential tariff reduction to illustrate both the potential of south-south liberalization and some of the particular challenges faced by South Asia. There is widespread agreement that deeper regional engagement in these areas will benefit the people of South Asia.